Chess for STEM: Development of Mind and Discipline in Study and at Leisure. - Mangala Krishnamurthy; John H. Sandy; Mary Ann Robbins (Issues in Science and Technology Librarianship)
The article discusses the chess service offered by the University of Alabama Rodgers Library for Science and Engineering for students, faculty and staff. Topics covered include the benefits provided by playing chess to the mental health of students, administrative details of chess at the library, and survey results showing use of chess service. Interesting facts about chess at the library are provided.